Search for copy number variants in chromosomes 15q11-q13 and 22q11.2 in obsessive compulsive disorder - Grabe Hans; Mössner Rainald; Chaste Pauline; Maier Wolfgang; Gennetier Aurélie; Moreno-; Delorme Richard; Ruhrmann Stephan; Falkai Peter; Mouren Marie-Christine; Leboyer Marion; Wagner Michael; et al. (BMC, 2010)
Abstract Background Obsessive-compulsive disorder (OCD) is a clinically and etiologically heterogeneous syndrome. The high frequency of obsessive-compulsive symptoms reported in subjects with the 22q11.2 deletion syndrome (DiGeorge/velocardiofacial syndrome) or Prader-Willi syndrome (15q11-13 deletion of the paternally derived chromosome), suggests that gene dosage effects in these chromosomal regions could increase risk for OCD. Therefore, the aim of this study was to search for microrearrangements in these two regions in OCD patients. Methods We screened the 15q11-13 and 22q11.2 chromosomal regions for genomic imbalances in 236 patients with OCD using multiplex ligation-dependent probe amplification (MLPA). Results No deletions or duplications involving 15q11-13 or 22q11.2 were identified in our patients. Conclusions Our results suggest that deletions/duplications of chromosomes 15q11-13 and 22q11.2 are rare in OCD. Despite the negative findings in these two regions, the search for copy number variants in OCD using genome-wide array-based methods is a highly promising approach to identify genes of etiologic importance in the development of OCD.